Polydimethylsiloxane membrane material with multi-component selective separation function

By developing a polydimethylsiloxane film material with multi-component selective separation function, the high operating cost and low purification effect caused by siloxane in biogas are solved, and the efficient separation effect of siloxane and CO2 is achieved.

CN119838451APending Publication Date: 2025-04-18NANJING CARBON RECYCLE BIOMASS ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510030126.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-08
Publication Date
2025-04-18

AI Technical Summary

Technical Problem

The presence of silicone in biogas leads to high operating costs and poor purification effects of biogas utilization equipment, and the existing membrane separation technology has not yet effectively solved this problem.

Method used

A polydimethylsiloxane film material with multi-component selective separation function was developed. By preparing nanowhisker silicon aluminum molecular sieve and polyvinylidene fluoride film, combining polydimethylsiloxane dispersion and casting film liquid, a film material with high permeability and selective separation function was prepared by casting method.

Benefits of technology

The simultaneous separation of silicone and CO2 from biogas is achieved, which improves the purification effect, reduces operating costs, and ensures high-quality preparation of membrane materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119838451A_ABST
    Figure CN119838451A_ABST
Patent Text Reader

Abstract

The invention relates to a polydimethylsiloxane membrane material with a multi-component selective separation function. The polydimethylsiloxane membrane material is characterized by being prepared by the following steps: (1) preparing a nano-whisker silicon-aluminum molecular sieve; (2) preparing a vinylidene fluoride film; (3) preparing a polydimethylsiloxane dispersion liquid; (4) preparing a polydimethylsiloxane membrane casting solution; and (5) preparing the polydimethylsiloxane membrane material, namely coating a vinylidene fluoride membrane with the polydimethylsiloxane membrane casting solution by adopting a tape casting method, drying at the temperature of 80 + / -5 DEG C, and reacting at the temperature of 120 + / -5 DEG C for 4 + / -0.5 hours to obtain the polydimethylsiloxane membrane material with a multi-component selective separation function. The membrane material disclosed by the invention has a multi-component selective separation function of simultaneously separating siloxane and CO2 from biogas.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a membrane technology, in particular to a membrane material technology for filtering siloxane in biogas, specifically to a polydimethylsiloxane membrane material with multi-component selective separation function. Background Art

[0002] At present, the biogas produced by anaerobic digestion of urban sludge and domestic waste contains volatile siloxane components. These siloxane components include cyclic and chain structures, mainly L2 (hexamethyldisiloxane), L3 (octamethyltrisiloxane), D4 (octamethylcyclotetrasiloxane), D5 (decamethylcyclopentasiloxane), etc. D4 is usually the main component, accounting for about 60% of the total siloxane content. Siloxane in biogas will seriously hinder the energy utilization of biogas, because siloxane will generate silicon oxide and other silicon-containing compounds in the process of participating in methane combustion, and adhere to the surface of gas engine combustion chamber components (such as cylinder heads, spark plugs, valves) or boiler heat exchange tubes, which will damage the working performance and service life of the engine and boiler, and will also poison and inactivate the flue gas denitrification catalyst, thereby causing serious adverse effects on the normal operation of biogas utilization equipment. In addition, in the process of extracting biogas from fuel cells for power generation, siloxane will also contaminate the electrode surface, causing voltage loss and lower power density. Therefore, purifying siloxane has become an important part of biogas utilization.

[0003] The purification methods for removing siloxanes from biogas mainly include adsorption, absorption, low-temperature condensation, catalytic oxidation, photocatalysis and biodegradation, but these methods have problems such as high operating costs and poor purification effects. The membrane separation method has the advantages of simple process flow, no secondary pollution and simple operation, and has been widely used in gas purification, but the research on the removal of siloxanes from biogas by this method has not been carried out or has rarely been reported. Summary of the invention

[0004] The purpose of the present invention is to invent a polydimethylsiloxane membrane material with multi-component selective separation function to solve the problems of high operating cost and poor purification effect caused by the lack of corresponding filtering membrane for siloxane in biogas.

[0005] The technical solution of the present invention is: A polydimethylsiloxane membrane material with multi-component selective separation function is characterized in that it is prepared by the following steps: (1) Preparation of nanocrystalline silicon-aluminum whisker molecular sieve: 0.5-5% by mass of nano-silicon dioxide, 0.5-5% sodium aluminate, 0.1-1% potassium hydroxide, 0.2-2% sodium hydroxide, 0.05-0.5% tetramethylammonium hydroxide, 0.05-0.5% aminopropyltriethoxysilane and water are mixed, stirred at 30±5°C for 24±6h to obtain a uniform gel solution, and then the gel solution is added to a high-pressure stainless steel reactor for hydrothermal reaction to generate nanocrystalline silicon-aluminum molecular sieve crystals at a temperature of 100-150°C and a time of 24-72h. After the hydrothermal reaction is completed, the solid particles in the reactor are filtered out, washed with deionized water, and vacuum dried at 120±10°C for 2±1h to obtain the nanocrystalline silicon-aluminum molecular sieve; (2) Preparation of vinylidene fluoride membrane: 5-20% by weight of polyvinylidene fluoride, 1-5% valerolactone, and 1-3% nano-whisker silica-alumina molecular sieve were dissolved in dimethylacetamide solvent, stirred at 50±10°C for 4±1h, vacuum-degassed for 12±6h, then poured onto polyethylene terephthalate non-woven fabric and scalded with a scraper to form a 100-200 μm thick membrane liquid, immersed in water for 72±12h, and then dried in the shade to obtain a vinylidene fluoride membrane material with a polyvinylidene fluoride support layer; (3) Preparation of polydimethylsiloxane dispersion: dissolve polydimethylsiloxane with a mass fraction of 5-20% and a molecular weight of 150,000 to 300,000 and 0.1-2% octylphenol polyoxyethylene ether in dichloromethane solvent to form a homogeneous solution, then add 50-100% water by mass of the solution, stir for 2-4 hours, evacuate and heat to 60±5°C and stir for 4-12 hours to form a polydimethylsiloxane dispersion; (4) preparing a polydimethylsiloxane casting solution: adding 1-10% by weight of ethyl orthosilicate, 0.1-0.5% by weight of chloroplatinic acid, and 0.5-3% by weight of tetraphenylhydroxyporphyrin to a polydimethylsiloxane dispersion, and performing ultrasonic dispersion to obtain a polydimethylsiloxane casting solution; (5) Preparation of polydimethylsiloxane membrane material: The polydimethylsiloxane casting liquid is coated on the polyvinylidene fluoride membrane by a casting method with a thickness of 10-30 μm, dried at 80±5°C, and reacted at 120±5°C for 4±1h to obtain a polydimethylsiloxane membrane material with multi-component selective separation function.

[0006] Beneficial effects of the present invention: The membrane material of the invention has a multi-component selective separation function capable of simultaneously separating siloxane and CO2 from biogas.

[0007] (1) The prepared polydimethylsiloxane membrane has high permeability to siloxane; (2) A functional component capable of transmitting and diffusing CO2 is added to the prepared polydimethylsiloxane membrane; (3) A hydrophilic nano-whisker silica-alumina molecular sieve material is added to the polyvinylidene fluoride support layer used to coat the polydimethylsiloxane membrane, so that the polydimethylsiloxane separation layer can be tightly filled in the polyvinylidene fluoride support layer, thereby ensuring the high-quality preparation of the separation layer membrane material.

[0008] (4) The tested permeation rates of methane were 14.23-35.72 KGPU, the permeation rates of carbon dioxide were 327.83-548.14 KGPU, and the permeation rates of D4 (octamethylcyclotetrasiloxane) were 1259.64-1687.22 KGPU. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 This is a scanning electron microscope image of the nano-whisker silicon aluminum molecular sieve of the present invention.

[0010] Figure 2 It is a scanning electron microscope image of the membrane material of the present invention. DETAILED DESCRIPTION

[0011] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.

[0012] like Figure 1-2 shown. Example

[0013] A polydimethylsiloxane membrane material with multi-component selective separation function is prepared by the following steps: (1) Preparation of nanocrystalline silicon aluminum whisker molecular sieve: Mix 3kg of nano-silicon dioxide, 3kg of sodium aluminate, 0.5kg of potassium hydroxide, 1kg of sodium hydroxide, 0.2kg of tetramethylammonium hydroxide, and 0.2kg of aminopropyl triethoxysilane with water, stir at 30°C for 24 hours to obtain a uniform gel solution, and then add the gel solution into a high-pressure stainless steel reactor for hydrothermal reaction. At 120°C and for 36 hours, nanocrystalline silicon aluminum whisker molecular sieve crystals are generated. After the hydrothermal reaction is completed, the solid particles in the reactor are filtered out, washed with deionized water, and vacuum dried at 120°C for 2 hours to obtain nanocrystalline silicon aluminum whisker molecular sieve. Figure 1 shown.

[0014] (2) Preparation of polyvinylidene fluoride membrane: 10 kg of polyvinylidene fluoride, 3 kg of valerolactone, and 2 kg of nano-whisker silica-alumina molecular sieve were dissolved in dimethylacetamide solvent, stirred at 50 °C for 4 h, and vacuumed to degas for 12 h. The mixture was then poured onto a polyethylene terephthalate non-woven fabric and scraped to form a 150 μm thick membrane liquid. The mixture was then soaked in water for 72 h and then dried in the shade to obtain a polyvinylidene fluoride membrane material with a polyvinylidene fluoride support layer.

[0015] (3) Preparation of polydimethylsiloxane dispersion: 15 kg of polydimethylsiloxane with a molecular weight of 150,000 to 300,000 and 1 kg of octylphenol polyoxyethylene ether are dissolved in dichloromethane solvent to form a homogeneous solution, and then 75% of water by mass of the solution is added, stirred for 3 hours, vacuumed and heated to 60°C and stirred for 8 hours to form a polydimethylsiloxane dispersion.

[0016] (4) Preparation of polydimethylsiloxane casting solution: 6 kg of ethyl orthosilicate, 0.3 kg of chloroplatinic acid and 1.8 kg of tetraphenylhydroxyporphyrin were added to the polydimethylsiloxane dispersion and ultrasonically dispersed to obtain the polydimethylsiloxane casting solution.

[0017] (5) Preparation of polydimethylsiloxane membrane material: The polydimethylsiloxane casting liquid is coated on the vinylidene fluoride membrane by casting method with a thickness of 20 μm, dried at 80°C, and reacted at 120°C for 4 hours to obtain a polydimethylsiloxane membrane material with multi-component selective separation function. Its scanning electron microscope structure is shown in the figure. Figure 2 shown.

[0018] The membrane material prepared in step (5) was tested: the permeation rate of methane was 35 KGPU, the permeation rate of carbon dioxide was 408 KGPU, and the permeation rate of D4, i.e. octamethylcyclotetrasiloxane, was 1400.23 KGPU. Example

[0019] A polydimethylsiloxane membrane material with multi-component selective separation function is prepared by the following steps: (1) Preparation of nanocrystalline silicon-aluminum whisker molecular sieve: 0.5 kg nano-silicon dioxide, 5 kg sodium aluminate, 0.1 kg potassium hydroxide, 2 kg sodium hydroxide, 0.05 kg tetramethylammonium hydroxide, 0.5 kg aminopropyltriethoxysilane and water were mixed, stirred at 35°C for 18 h to obtain a uniform gel solution, and then the gel solution was added to a high-pressure stainless steel reactor for hydrothermal reaction to generate nanocrystalline silicon-aluminum molecular sieve crystals at 100°C for 72 h. After the hydrothermal reaction, the solid particles in the reactor were filtered out, washed with deionized water, and vacuum dried at 130°C for 3 h to obtain nanocrystalline silicon-aluminum molecular sieve; (2) Preparation of vinylidene fluoride membrane: 5 kg of polyvinylidene fluoride, 5 kg of valerolactone, and 1 kg of nano-whisker silica-alumina molecular sieve were dissolved in dimethylacetamide solvent, stirred at 60 ° C for 3 h, vacuumed and degassed for 18 h, then poured on polyethylene terephthalate non-woven fabric and scalded with a scraper to form a 100 μm thick membrane liquid, immersed in water for 84 h, and then dried in the shade to obtain a vinylidene fluoride membrane material with a polyvinylidene fluoride support layer; (3) Preparation of polydimethylsiloxane dispersion: 5 kg of polydimethylsiloxane with a molecular weight of 150,000 to 300,000 and 2 kg of octylphenol polyoxyethylene ether were dissolved in dichloromethane solvent to form a homogeneous solution, and then 50% of the mass of water was added, stirred for 2 h, vacuumed and heated to 65 ° C and stirred for 4 h to form a polydimethylsiloxane dispersion; (4) preparing a polydimethylsiloxane casting solution: adding 1 kg of ethyl orthosilicate, 0.5 kg of chloroplatinic acid, and 0.5 kg of tetraphenylhydroxyporphyrin to a polydimethylsiloxane dispersion, and performing ultrasonic dispersion to obtain a polydimethylsiloxane casting solution; (5) Preparation of polydimethylsiloxane membrane material: The polydimethylsiloxane casting liquid is coated on the polyvinylidene fluoride membrane by a casting method with a thickness of 10 μm, dried at 85°C, and reacted at 125°C for 5 hours to obtain a polydimethylsiloxane membrane material with multi-component selective separation function.

[0020] The tested permeation rate of methane was 14.23 KGPU, the permeation rate of carbon dioxide was 548.14 KGPU, and the permeation rate of D4, i.e. octamethylcyclotetrasiloxane, was 1259.64 KGPU. Example

[0021] A polydimethylsiloxane membrane material with multi-component selective separation function is prepared by the following steps: (1) Preparation of nanocrystalline silicon aluminum whisker molecular sieve: 5 kg nano silicon dioxide, 0.5 kg sodium aluminate, 1 kg potassium hydroxide, 0.2 kg sodium hydroxide, 0.5 kg tetramethylammonium hydroxide, 0.05 kg aminopropyl triethoxysilane and water were mixed, stirred at 25 ° C for 30 hours to obtain a uniform gel solution, and then the gel solution was added to a high-pressure stainless steel reactor for hydrothermal reaction to generate nanocrystalline silicon aluminum whisker molecular sieve crystals at 150 ° C for 24 hours. After the hydrothermal reaction, the solid particles in the reactor were filtered out, washed with deionized water, and vacuum dried at 110 ° C for 1 hour to obtain nanocrystalline silicon aluminum whisker molecular sieve; (2) Preparation of vinylidene fluoride membrane: 20 kg of polyvinylidene fluoride, 1 kg of valerolactone, and 3 kg of nano-whisker silica-alumina molecular sieve were dissolved in dimethylacetamide solvent, stirred at 40 ° C for 5 h, vacuumed and degassed for 6 h, then poured onto polyethylene terephthalate non-woven fabric and scalded with a scraper to form a 200 μm thick membrane liquid, immersed in water for 60 h, and then dried in the shade to obtain a vinylidene fluoride membrane material with a polyvinylidene fluoride support layer; (3) Preparation of polydimethylsiloxane dispersion: 20 kg of polydimethylsiloxane with a molecular weight of 150,000 to 300,000 and 0.1 kg of octylphenol polyoxyethylene ether were dissolved in dichloromethane solvent to form a homogeneous solution, and then 100% water by mass of the solution was added, stirred for 4 hours, vacuumed and heated to 55°C and stirred for 12 hours to form a polydimethylsiloxane dispersion; (4) preparing a polydimethylsiloxane casting solution: adding 10 kg of ethyl orthosilicate, 0.1 kg of chloroplatinic acid, and 3 kg of tetraphenylhydroxyporphyrin to a polydimethylsiloxane dispersion, and performing ultrasonic dispersion to obtain a polydimethylsiloxane casting solution; (5) Preparation of polydimethylsiloxane membrane material: The polydimethylsiloxane casting liquid is coated on the polyvinylidene fluoride membrane by a casting method with a thickness of 30 μm, dried at 75°C, and reacted at 115°C for 3 hours to obtain a polydimethylsiloxane membrane material with multi-component selective separation function.

[0022] Scanning electron microscopy and scanning electron microscopy of the membrane materials prepared in Examples 2 and 3 Figure 2 They are similar, so they are no longer provided.

[0023] The parts not involved in the present invention are the same as the prior art or can be implemented by using the prior art.

Claims

1. A polydimethylsiloxane membrane material with multi-component selective separation function, characterized in that: It is prepared by the following steps: (1) Preparation of nanocrystalline silicon-aluminum whisker molecular sieve: 0.5-5% by mass of nano-silicon dioxide, 0.5-5% sodium aluminate, 0.1-1% potassium hydroxide, 0.2-2% sodium hydroxide, 0.05-0.5% tetramethylammonium hydroxide, 0.05-0.5% aminopropyltriethoxysilane and water are mixed, stirred at 30±5°C for 24±6h to obtain a uniform gel solution, and then the gel solution is added to a high-pressure stainless steel reactor for hydrothermal reaction to generate nanocrystalline silicon-aluminum molecular sieve crystals at a temperature of 100-150°C and a time of 24-72h. After the hydrothermal reaction is completed, the solid particles in the reactor are filtered out, washed with deionized water, and vacuum dried at 120±10°C for 2±1h to obtain the nanocrystalline silicon-aluminum molecular sieve; (2) Preparation of vinylidene fluoride membrane: 5-20% by weight of polyvinylidene fluoride, 1-5% valerolactone, and 1-3% nano-whisker silica-alumina molecular sieve were dissolved in dimethylacetamide solvent, stirred at 50±10°C for 4±1h, vacuum-degassed for 12±6h, then poured onto polyethylene terephthalate non-woven fabric and scalded with a scraper to form a 100-200 μm thick membrane liquid, immersed in water for 72±12h, and then dried in the shade to obtain a vinylidene fluoride membrane material with a polyvinylidene fluoride support layer; (3) Preparation of polydimethylsiloxane dispersion: dissolve polydimethylsiloxane with a mass fraction of 5-20% and a molecular weight of 150,000 to 300,000 and 0.1-2% octylphenol polyoxyethylene ether in dichloromethane solvent to form a homogeneous solution, then add 50-100% water by mass of the solution, stir for 2-4 hours, evacuate and heat to 60±5°C and stir for 4-12 hours to form a polydimethylsiloxane dispersion; (4) preparing a polydimethylsiloxane casting solution: adding 1-10% by weight of ethyl orthosilicate, 0.1-0.5% by weight of chloroplatinic acid, and 0.5-3% by weight of tetraphenylhydroxyporphyrin to a polydimethylsiloxane dispersion, and performing ultrasonic dispersion to obtain a polydimethylsiloxane casting solution; (5) Preparation of polydimethylsiloxane membrane material: The polydimethylsiloxane casting liquid is coated on the polyvinylidene fluoride membrane by a casting method with a thickness of 10-30 μm, dried at 80±5°C, and reacted at 120±5°C for 4±1h to obtain a polydimethylsiloxane membrane material with multi-component selective separation function.

2. The membrane material according to claim 1, characterized in that: When preparing nanocrystalline whisker silica-alumina molecular sieve, 3% by mass of nano-silica, 3% sodium aluminate, 0.5% potassium hydroxide, 1% sodium hydroxide, 0.2% tetramethylammonium hydroxide, and 0.2% aminopropyltriethoxysilane are mixed with water, stirred at 30°C for 24 hours to obtain a uniform gel solution, and then the gel solution is added to a high-pressure stainless steel reactor for hydrothermal reaction to generate nanocrystalline whisker silica-alumina molecular sieve crystals at 120°C for 36 hours. After the hydrothermal reaction is completed, the solid particles in the reactor are filtered out, washed with deionized water, and vacuum dried at 120°C for 2 hours to obtain the nanocrystalline whisker silica-alumina molecular sieve.

3. The membrane material according to claim 1, characterized in that: When preparing the polyvinylidene fluoride membrane, 10% by weight of polyvinylidene fluoride, 3% valerolactone, and 2% nanowhisker silica-alumina molecular sieve were dissolved in dimethylacetamide solvent, stirred at 50°C for 4 hours, and vacuumed to degas for 12 hours. Then, the solution was poured onto a polyethylene terephthalate non-woven fabric and scraped with a scraper to form a 150 μm thick membrane liquid. The solution was soaked in water for 72 hours and then dried in the shade to obtain a polyvinylidene fluoride membrane material with a polyvinylidene fluoride support layer.

4. The membrane material according to claim 1, characterized in that: When preparing the polydimethylsiloxane dispersion, polydimethylsiloxane with a mass ratio of 15% and a molecular weight of 150,000 to 300,000 and 1% octylphenol polyoxyethylene ether are dissolved in dichloromethane solvent to form a homogeneous solution, and then water (75% by mass of the solution) is added, stirred for 3 hours, vacuumed and heated to 60°C and stirred for 8 hours to form a polydimethylsiloxane dispersion.

5. The membrane material according to claim 1, characterized in that: When preparing the polydimethylsiloxane casting solution, 6% by weight of ethyl orthosilicate, 0.3% of chloroplatinic acid and 1.8% of tetraphenylhydroxyporphyrin were added to the polydimethylsiloxane dispersion, and ultrasonic dispersion was performed to obtain the polydimethylsiloxane casting solution.

6. The membrane material according to claim 1, characterized in that: When preparing the polydimethylsiloxane membrane material, the polydimethylsiloxane casting liquid is coated on the vinylidene fluoride membrane by a casting method with a thickness of 20 μm, dried at 80°C, and reacted at 120°C for 4 hours to obtain a polydimethylsiloxane membrane material with multi-component selective separation function.